Meningkatkan Kemampuan Mengenal Bentuk Geometri Anak Usia Dini 5-6 Tahun Menggunakan Media Rumah Pintar di KB Melati VI - Fartillah, Erna; Elnawati, Elnawati; Awal Maulana, Redi (PT. Alahyan Publisher Sukabumi, 2025)
This research aims to improve the ability of early childhood 5-6 years old to recognize geometric shapes using the Smart Home learning media at KB Melati VI. This research was carried out using the Classroom Action Research (PTK) method which consisted of four stages, namely planning, implementation, observation, and reflection. The research was conducted in three cycles: pre-cycle, cycle I, and cycle II, with 15 children aged 5-6 years. At the planning stage, Rumah Pintar media is designed to contain various geometric shapes that are interesting, interactive, and easy for children to understand. The implementation of learning uses a play-by-learning approach, where children are invited to recognize, group, and name geometric shapes through fun activities. Data were collected through observation, interviews, and documentation, then analyzed in a quantitative descriptive manner. The results of the study showed a significant increase in children's ability to recognize geometric shapes. In the pre-cycle stage, the average child's ability reached 45%, then increased to 70% in cycle I, and reached 90% in cycle II. This shows that the effective use of Rumah Pintar media can increase children's interest in learning and ability to recognize geometric shapes. This study concludes that Rumah Pintar media is an effective learning tool in improving early childhood cognitive abilities, especially in recognizing geometric shapes. The researcher recommends the use of similar media for the development of other cognitive aspects and encourages the innovation of learning media that is in accordance with the characteristics of early childhood.